Advances in global leadership. Vol. 11 - Osland, Joyce; Mendenhall, Mark E., 1956-; Li, Ming, active 2018 (Advances in global leadership, 2018)
This volume continues to advance both global leadership research and practice by bridging and integrating conceptual, empirical and practitioner perspectives to provide a deeper understanding of this rapidly growing field of study. Part I presents innovative foundational research on global leadership processes, systematic bibliometric literature reviews, and a holistic approach to talent selection. Part II, the Practitioner's Corner, contains papers submitted in response to our call for global leadership development in university settings. The editors conclude with directions for future research as well as benchmarks for university global leadership programs and study abroad initiatives. This volume is a wonderful primer for anyone tasked with designing and assessing global leadership development programs for students. The 'Advances in Global Leadership' series,with its finger firmly on the pulse of this exciting field, is a must-read book for scholars and practitioners alike.